The Connection between Oral Health and Systemic Health: How Dentistry Can Help Prevent Chronic Diseases - Majid Mohammad Alshammari; Nasser mohammedaldhafeeri; Mohammed Khaled Almutlaq; Mohammed Khalif Aldhafeeri; Hamad Ghafel Aldhfeeri; Nasser Siran Alharbi; Yazeed aied Alrawili (International Journal of Medical Toxicology and Legal Medicine, 2024)
Recent studies have increasingly demonstrated that oral health is closely linked to systemic health, with oral diseases playing a role in the risk and advancement of various chronic health issues. This article examines the relationship between oral health and systemic illnesses like cardiovascular disease, diabetes, respiratory issues, and various cancers. We also explore the preventative function dentistry can serve in addressing these risks, emphasizing both the biological processes at play and the possibilities for early interventions within dental environments.